Cnaphalocrocis medinalis Moths Decide to Migrate when Suffering Nutrient Shortage on the First Day after Emergence - Guo, Jia-Wen (Insects, 2019)
Migration is a costly strategy in terms of reproduction output. Competition for limited internal resources leads to physiological management of migration-reproduction trade-offs in energy allocation. Migratory insects must choose to determine to allocate energy into reproduction or migration when confronted insufficient energy supply. Although nutrient shortage is known to stimulate insect migration to escape deteriorating habitat, little is known about when and how migratory insects make decisions when confronted by a nutritional shortage. Here Cnaphalocrocis medinalis (Lepidoptera: Pyralidae), a migratory rice pest in eastern Asia, was used to study the effects of starvation on reproductive traits, behavioral traits and energy allocation. The result showed that one or two days’ starvation before preoviposition did not significantly reduce the fertility (total egg per female laid) and flight capability (flight duration and distance) of both sexes C. medinalis. The preoviposition period was extended significantly only if moths were starved starting on the first day after emergence. Also, take-off percentage of moths starved since their first day increased significantly, and continued to increase even if supplemental nutrients were supplied as honey solution in later days. Moths starved on the first day appeared to allocate or transfer triglycerides into the thorax to maintain the migration process: the quantity of thoracic triglycerides did not differ with age, but abdominal triglycerides decreased with age if starvation continued. These results indicate that the first day post-emergence is a critical period for C. medinalis to decide to migrate or not in response to lack of food. This furthers our understanding of the population dynamics of migratory insects under natural conditions.